1998
DOI: 10.1083/jcb.143.5.1167
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Long Chain Fatty Acid Elongation in the Trafficking of Secretory Vesicles in Yeast

Abstract: Members of the synaptobrevin/VAMP family of v-SNAREs are thought to be essential for vesicle docking and exocytosis in both lower and higher eukaryotes. Here, we describe yeast mutants that appear to bypass the known v-SNARE requirement in secretion. Recessive mutations in either VBM1 or VBM2, which encode related ER-localized membrane proteins, allow yeast to grow normally and secrete in the absence of Snc v-SNAREs. These mutants show selective alterations in protein transport, resulting in the differential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
145
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(159 citation statements)
references
References 71 publications
13
145
0
1
Order By: Relevance
“…The high-density vesicles contain invertase and acid phosphatase and intersect with the endosomal system, whereas the low-density vesicles contain Pma1 and glucanase and are directly transported to the cell surface without intersection with endosomes [7]. Elongase mutants on the other hand fail to generate these two vesicle populations and instead missort invertase and acid phosphatase into the Pma1 containing vesicle [30]. Whether the stability of Pma1, once delivered to the plasma membrane, is affected by the mixing of the two vesicle populations is presently not known.…”
Section: Coupling Of H D -Atpase Biogenesis To Sphingolipid Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The high-density vesicles contain invertase and acid phosphatase and intersect with the endosomal system, whereas the low-density vesicles contain Pma1 and glucanase and are directly transported to the cell surface without intersection with endosomes [7]. Elongase mutants on the other hand fail to generate these two vesicle populations and instead missort invertase and acid phosphatase into the Pma1 containing vesicle [30]. Whether the stability of Pma1, once delivered to the plasma membrane, is affected by the mixing of the two vesicle populations is presently not known.…”
Section: Coupling Of H D -Atpase Biogenesis To Sphingolipid Synthesismentioning
confidence: 99%
“…Better understanding of the role that these asymmetrical C26-containing lipids have on protein sorting to the plasma membrane is important because elo3D mutant cells not only affect Pma1 stability but also show delayed ER to Golgi transport of the GPI-anchored protein Gas1 and defective surface transport of an artificial cargo protein [30,39]. We have previously characterized the biophysical properties of an inositol glycerophospholipid with a C26 fatty acid in position sn-1 and shown that this lipid is very potent in stabilizing highly curved membrane structures [40].…”
Section: What Is the Function Of C26-containing Lipids?mentioning
confidence: 99%
“…The sites of exocytosis are also postulated to determine the shape of the growing hypha (Bartnicki-Garcia et al, 1989;Bartnicki-Garcia, 1990;Gierz and Bartnicki-Garcia, 2001); thus, it was of particular interest to follow membrane trafficking by using fusion proteins of the synaptobrevin homologue SYNA, an exocytic SNARE (Gerst, 1997). Given that SYNA is a member of a family of prototypic markers for exocytic vesicles (Protopopov et al, 1993;Gerst, 1997;David et al, 1998), it is strongly predicted to be a component of exocytic vesicles that becomes a transient component of the plasma membrane when exocytosis occurs, and then is recycled by endocytosis. Completely consistent with these predictions, we have found that SYNA localizes to small dots in the cytoplasm, to the Spitzenkö rper and to the plasma membrane at the hyphal apex.…”
Section: Exocytosis Endocytosis and Hyphal Morphogenesismentioning
confidence: 99%
“…Interestingly, the suppressor mutations of this phenotype map to the VBM1 and VBM2 genes, which are identical to ELO 2 and 3, whose gene products are involved in the elongation of fatty acids to generate the long-chain fatty acids required for ceramide synthesis [71]. While attempting to understand the role of sphingolipids in the growth and secretion phenotypes of the snc mutant cells (see below) cells, Marash and Gerst found that treating the cells with ceramide precursors or analogs restores normal growth at restrictive temperatures [72].…”
Section: Sphingolipids In Endocytosis and Exocytosismentioning
confidence: 99%
“…The SNC1 and SNC2 genes encode snc1p and snc2p respectively, which are archetypal v-SNARES involved in the exocytosis process [68,69,71,74]. The mutants cease growth at 38°C, and at 37°C they accumulate secretory vesicles and show defective protein secretion.…”
Section: Sphingolipids In Endocytosis and Exocytosismentioning
confidence: 99%